Perceived Stress and Short-Form Video Application Addiction: A Moderated Mediation Model - Liu, Yinbo; Ni, Xiaoli; Niu, Gengfeng (Frontiers in Psychology, 2021)
Nowadays, short-form video applications have become increasingly popular due to their strong appeal to people, especially among college students. With this trend, the phenomenon of short-form video application addiction (SVA) also become prominent, which is a great risk for individuals’ health and adaptation. Against this background, the present study aimed to examine the association between perceived stress and SVA addiction, as well as its mechanism—the mediating role of self-compensation motivation (SCM) and the moderating role of shyness. A total of 896 Chinese college students was recruited to complete a set of questionnaires on perceived stress (PS), SCM, shyness, and short-form video applications. The results show that PS was positively associated with SVA, and SCM partially mediated this association. In addition, both the direct association between PS and SVA and the indirect effect of SCM were moderated by shyness and were stronger for individuals with higher levels of shyness. The results could not only deepen our understanding of the underlying factors of SVA but also provide suggestions for relevant prevention and intervention procedures.